2010
DOI: 10.1002/biof.120
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate induced increase in mitochondrial electron transport chain complex IV activity in human astrocytoma cells: Implications for mitochondrial cytopathies and neurodegenerative diseases

Abstract: Mitochondrial encephalomyopathies resulting from electron transport chain (ETC) dysfunction can present with a wide spectrum of clinical manifestations having significant neuropathology and a progressive nature. Despite advances in diagnosis of ETC disorders, treatment still remains inadequate. A recent study in fibroblasts and myoblasts revealed the ability of fibrate treatment to correct ETC enzyme deficiencies. Therefore, fibrates may represent potential therapeutic agents to correct the neurological ETC im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Consistent with the presumed mode of action of BZ, positive effects of treatment were only achieved in cell lines that exhibited some level of residual RC function, i.e., when the disease causing mutations did not lead to highly unstable or absent mutant protein [105]. Further studies from other groups confirmed that BZ could upregulate the activities of RC complex I, III, and IV in human skin fibroblasts, and displayed similar effects in a variety of cell lines including HeLa, HEK293, bone marrow-derived cells, and human brain astrocytoma cells [106,107,108]. In a compared study of patients’ fibroblasts harboring mutations in Sco2 or Surf1 gene , it was found that treatment with BZ could correct COX activity in the Sco2-deficient cell line, which exhibited partial COX deficiency, but not in the Surf1 mutant, which was almost devoid of residual enzyme activity [107].…”
Section: Bezafibratementioning
confidence: 99%
“…Consistent with the presumed mode of action of BZ, positive effects of treatment were only achieved in cell lines that exhibited some level of residual RC function, i.e., when the disease causing mutations did not lead to highly unstable or absent mutant protein [105]. Further studies from other groups confirmed that BZ could upregulate the activities of RC complex I, III, and IV in human skin fibroblasts, and displayed similar effects in a variety of cell lines including HeLa, HEK293, bone marrow-derived cells, and human brain astrocytoma cells [106,107,108]. In a compared study of patients’ fibroblasts harboring mutations in Sco2 or Surf1 gene , it was found that treatment with BZ could correct COX activity in the Sco2-deficient cell line, which exhibited partial COX deficiency, but not in the Surf1 mutant, which was almost devoid of residual enzyme activity [107].…”
Section: Bezafibratementioning
confidence: 99%